Miyun Yuanwu 密雲圓悟 (1567–1642) and His Impact on 17th-Century Buddhism - Bingenheimer, Marcus (Religions, 2023)
This paper relies on the dataset “Historical Social Network of Chinese Buddhism” (Ver. 2021-06). The focus is on the period between c. 1570 and 1700 CE. We argue that the actor who was most influential for institutional Buddhism in the 17th century was not one of the “four great monks of the late Ming” but rather Miyun Yuanwu 密雲圓悟 (1566–1642). The network illustrates how Miyun’s Tiantong branch 天童派 of the Linji School became the dominant Chan lineage in China and beyond. The main results of this study are: (1) the data corroborate the assumption that (at least) monastic Buddhism declined between c. 1420 and 1570. (2) The network view de-emphasizes the importance of the ‘four famous late Ming eminent monks’ for the development of 17th-century Buddhist monasticism. (3) The data align well with a suggestion by Jiang Wu to distinguish two different stages in the development of late Ming Buddhism. The first is characterized by the “late Ming revival,” led by figures such as Yunqi Zhuhong, Zibo Zhenke, and Hanshan Deqing; the second phase is the organization of orthopraxy around the Chan lineage discourse dominated by Miyun Yuanwu and his students. (4) For the 17th century, the network data clearly shows the centrality of Miyun Yuanwu and his network.